STRATEGI DAKWAH PESANTREN LUHUR AL-HUSNA DALAM MENJAGA TOLERANSI BERAGAMA DI KOTA SURABAYA - Muhammad Hamdan Yuwafik; Abdul Muhid (MUHARRIK: Jurnal Dakwah dan Sosial, 2020)
This paper attempts to potrait the da'wah strategy of the Luhur Al-Husna Islamic Boarding School in maintaining religious tolerance in the city of Surabaya, as well as its correlation with the Al-Madkhal Ila Ilmi Dakwah book by Al-Bayanuni. The following article is the results of direct field study, with a descriptive analysis approach to the Da'wah strategy model of the Luhur Al-Husna Islamic Boarding School in maintaining religious tolerance. The results of the study indicate that the da'wah strategies used by the Luhur Al-Husna Islamic Boarding School are dialogue, cultural exchange and living together. In addition, the Luhur Al-Husna Islamic Boarding School also uses three da'wah strategies according to Al-Bayanunni, namely al-athifi, al-aqly, and al-hissi. The Da'wah strategy of the Luhur Al-Husna Islamic Boarding School can be said to be successful in maintaining tolerance because it is able to survive and continue to exist today.